Transcriptional control of visual neural circuit development by GS homeobox 1. - Alexandra R Schmidt; Haiden J Placer; Ishmael M Muhammad; Rebekah Shephard; Regina L Patrick; Taylor Saurborn; Eric J Horstick; Sadie A Bergeron (PLoS Genetics, 2024)
As essential components of gene expression networks, transcription factors regulate neural circuit assembly. The homeobox transcription factor encoding gene, gs homeobox 1 (gsx1), is expressed in the developing visual system; however, no studies have examined its role in visual system formation. In zebrafish, retinal ganglion cell (RGC) axons that transmit visual information to the brain terminate in ten arborization fields (AFs) in the optic tectum (TeO), pretectum (Pr), and thalamus. Pretectal AFs (AF1-AF9) mediate distinct visual behaviors, yet we understand less about their development compared to AF10 in the TeO. Using gsx1 zebrafish mutants, immunohistochemistry, and transgenic lines, we observed that gsx1 is required for vesicular glutamate transporter, Tg(slc17a6b:DsRed), expression in the Pr, but not overall neuron number. gsx1 mutants have normal eye morphology, yet they exhibit impaired visual ability during prey capture. RGC axon volume in the gsx1 mutant Pr and TeO is reduced, and AF7 that is active during feeding is missing which is consistent with reduced hunting performance. Timed laser ablation of Tg(slc17a6b:DsRed)-positive cells reveals that they are necessary for AF7 formation. This work is the first to implicate gsx1 in establishing cell identity and functional neural circuits in the visual system.